Supplementation of Moringa (Moringa oleifera) Leaf Meal on Growth Performance of Bileh Fish (Rasbora sp.) - Kombih, Annisa Alrany Pirdah; Diana, Farah; Diansyah, Sufal; Islama, Dini (Universitas Teuku Umar, 2024)
Bileh fish (Rasbora sp.) is one type of Acehnese freshwater fish that is very popular with the public because it has a delicious and savory taste. The main objective in conducting this study was to determine the effect of using Moringa (Moringa oleifera) leaf flour as a supplement to commercial feed on the growth of bileh fish (Rasbora sp.). This study used a completely randomized design consisting of four treatments and three replications each. The doses of moringa flour used as the test treatment consisted of; P0 (control) = 0% moringa flour, P1 = 20% moringa flour, P2 = 30% moringa flour, P3 = 40% moringa flour. The parameters observed were proximate test, absolute weight growth, specific growth rate, absolute length growth, survival rate, feed efficiency and water quality consisting of temperature and pH. The results of analysis of variance (ANOVA) showed that the dosing of moringa flour in feed had a significant effect on absolute weight growth, absolute length growth and specific growth rate, but had no significant effect on the survival rate of bileh fish juvenile. The best dose of moringa leaf flour to increase the growth of bileh fish is the P3 treatment (moringa leaf flour) with an absolute weight growth value of 1.27 grams, absolute length growth of 5.93cm, and a survival rate in the P3 treatment of 98%.